'Complexity in simplicity': the effects of visual complexity on consumers' comprehension of product innovations. (27th October 2021) - Cheng, Peiyao; Mugge, Ruth; Bont, Cees De
Designers are frequently involved in embodying product innovations. It is challenging to embody really new products (RNPs) because consumers often have difficulty comprehending them. This study explores the value of visual complexity for designing RNPs. In study 1, an experiment was conducted (n = 77) to test the effects of visual complexity on consumers' comprehension of incrementally new products (INPs) and RNPs. The results revealed different effects for INPs and RNPs. Specifically, a more complex appearance triggers congruence with the functions of a RNP, which facilitates consumers' comprehension. For INPs, no effects for visual complexity were found. Based on the positive effect of visual simplicity on consumers' aesthetic response to product design, the design strategy 'complexity in simplicity' is proposed. In study 2, we asked experienced designers (n = 6) to apply this design strategy. Results showed that they can design RNPs using the 'complexity in simplicity' and possible ways to achieve this are explained.